Ryzyko podatkowe w działalności przedsiębiorstwa - Poszwa, Michał (Tax Risk in Company Management, 2005)
Tax system is a source of an additional risk in company management. The fiscal duty can be accomplished by taking into account income or in the simply way - by stating the figures. Most of all the usage of different methods or ways of taxation brings various net present values. It means there is a necessity of stating the premises concerning the choice of the best forms of income taxation. However, the greatest financial advantages can be achieved by the accommodation taxation form and particular stages of investment operating and accomplishing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 34-38